The Relationship Between Leg Muscle Strength and 100-Meter Running Speed in High School Athletes - Dahri, Suci Yati; Prawibowo, Muhammad; Mardiansyah, Muhammad Alfin; Alhafi, Muhammad Iqbal; Saputra, Ilpan (Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to determine how strong the leg muscle strength is with the 100-meter running speed in class X students at SMA Negeri 1 Kepenuhan Hulu. The hypothesis in this study is